The Impact of New Media in the Information Society Era - Lili Anggraini (AGUSPATI RESEARCH INSTITUTA, 2023)
The development of computer technology is very fast, both in terms of hardware and software as well as application packages that are used as a tool to process data and provide detailed, accurate, and efficient, information. Designing, creating, and implementing an in implementing the system in the data collection of teaching and learning schedules is very important in the world of education, because it facilitates and facilitates data processing activities, and data searches related to the learning schedule needed in decision making. Raksana Medan Private High School has a problem in managing scheduling because uses a manual scheduling system. Therefore with an informatystem scheduling teaching and learning with Rapid Application n Development method (RAD can increase the effectiveness in accordance with the needs of the SMA Raksana in Medan so that scheduling activities can be implemented properly. Keywords: Information Systems, Scheduling, Rapid Application Development